Graphic symbols terminology: a call for a consensus - Pampoulou, Eliada (My University, 2017)
Graphic symbols, such as the Picture Communication Symbols, Makaton and Widgit, have been traditionally used in the field of augmentative and alternative communication (AAC) in order to support people with little or no functional speech. The paper aims to discuss these issues. Design/methodology/approach However, given the fact that the terminology remains contested in the existing literature as well as the multidisciplinary nature surrounding graphic symbols, in more recent years and the number of terms used in different fields, it is vital that the terminology of graphic symbols is revisited again. Findings In the last section of the paper, a definition of graphic symbols is proposed. Originality/value The value of this paper lies in the fact that while field of graphic symbols have been used in the AAC for more than 30 years, there is still no consensus regarding the meaning of the terminology used.
Keywords: Semiotics; Definition; AAC; Graphic symbols; Manual symbols; Spoken symbols